Time of Stroke Onset in Coronavirus Disease 2019 Patients Around the Globe: A Systematic Review and Analysis - Valencia-Enciso, Natalia (J Stroke Cerebrovasc Dis, 2020)
INTRODUCTION: Coronavirus disease 2019 has been associated with stroke, particular characteristics of these patients are not fully understood. The adequate management of these patients depends on the comprehension of factors such as temporality, clinical presentation and etiology. We hypothesize there is an important temporal relationship between COVID-19 severity and stroke onset. METHODS: a systematic review of the available literature was conducted using Pubmed and Scopus, studies reporting patients with Coronavirus disease 19 and stroke were included. Clinical, sociodemographic and laboratory characteristics of patients were extracted and analyzed. RESULTS: Forty-seven studies and 176 patients were included, with a mean age of 63.1 years (SD= 16 n=122), most of them were males (63.2% n=171). The most frequent etiology was cryptogenic 40.9% n=66), and a mean National Institute of Health Stroke Scale of 14.4 points was found (SD= 8.6 n=73). Large vessel occlusion was reported in 65.9% patients (n=91) and these patients were younger with greater stroke severity. D-dimer, C-reactive protein, fibrinogen, ferritin and lactate dehydrogenase were elevated in most patients with reported findings. Most patients had severe Coronavirus disease 2019. The mean time from onset of respiratory symptoms to stroke was 9 days (SD=9.9), the shortest time was noted in those with mild and moderate disease. CONCLUSIONS: There is a trend between the severity of Coronavirus disease 2019 and time to stroke onset. Also, age and stroke severity were found to be related to the development of large vessel occlusion. Inflammation and hypercoagulability markers are elevated in this disease, we propose to not discard hypercoagulability secondary to severe acute respiratory syndrome-coronavirus-2 as an underlying cause of stroke in these patients.